Dasar-dasar Pendidikan : Study kasus Dasar Sosiologi dan kultural dalam pendidikan - Rohmah, Ayyu Nur (Maliki Interdisciplinary Journal, 2025)
We all know that education is a part of human existence. In the process of forming society, education plays a role in the process of realizing the fundamental pillars of society. Sociology is a science that studies the relationships between people in groups and thei social structures. Culture and education are interrelated, and culture can be maintained or developed by passing it on from generation to generation througt formal and non formal education. This research was conducted with the aim of explaining sociology in education, this is needed as one of the fundamentals of education and the basis for implementing the sociology of education in Indonesia. This is based on sociology and plays an important role in education as a reference or basis for achieving educational goals. Educational concepts and theories provide guidance for teachers to develop habits of, cooperation, harmony, friendship, mutual assistance and mutual respect in their students. Considering the urgency of the relationship between dynamics and socioculture, educational sociology seeks to apply scientific analysis to understand educational phenomena in the context of sociocultural change. The first step is to establish a process that explains the nature of culture as a means of growth and development of educational existence for members of society. As an educational tool, it fulfills institutional tasks in accordance with the laws of social development.